Effect of Pore Characteristics and Alkali Treatment on the Physicochemical and Biological Properties of a 3D-Printed Polycaprolactone Bone Scaffold - Janmohammadi, Mahsa; Nourbakhsh, Mohammad Sadegh; Bahraminasab, Marjan; Tayebi, Lobat (ACS omega, 2023)
Polycaprolactone scaffolds were designed and 3D-printed with different pore shapes (cube and triangle) and sizes (500 and 700 μm) and modified with alkaline hydrolysis of different ratios (1, 3, and 5 M). In total, 16 designs were evaluated for their physical, mechanical, and biological properties. The present study mainly focused on the pore size, porosity, pore shapes, surface modification, biomineralization, mechanical properties, and biological characteristics that might influence bone ingrowth in 3D-printed biodegradable scaffolds. The results showed that the surface roughness in treated scaffolds increased compared to untreated polycaprolactone scaffolds ( = 2.3-10.5 nm and = 17- 76 nm), but the structural integrity declined with an increase in the NaOH concentration especially in the scaffolds with small pores and a triangle shape. Overall, the treated polycaprolactone scaffolds particularly with the triangle shape and smaller pore size provided superior performance in mechanical strength similar to that of cancellous bone. Additionally, the in vitro study showed that cell viability increased in the polycaprolactone scaffolds with cubic pore shapes and small pore sizes, whereas mineralization was enhanced in the designs with larger pore sizes. Based on the results obtained, this study demonstrated that the 3D-printed modified polycaprolactone scaffolds exhibit a favorable mechanical property, biomineralization, and better biological properties; therefore, they can be applied in bone tissue engineering.